Robert H. Michel : leading the Republican House minority - Mackaman, Frank H.; Kelly, Sean Q. (Congressional leaders., 2019)
"Leading the Republican House Minority examines the public service and legacy of Robert H. Michel, who had a thirty-eight-year career in the House of Representatives, capped by fourteen years as Republican Leader. His career in office is distinguished by one factor above all: the Republicans failed to gain the majority in the House of Representatives during his nearly four decades in Congress. His party's status as the minority party accounted for Michel's early legislative experience, his rise through the leadership ranks of the House Republicans, his leadership style and eventual challenges to that style, and, ultimately, to his retirement in 1995. Minority status did not preclude political and legislative achievement, however. His central Illinois constituents elected Michel nineteen times to his seat in the House. In turn, his Republican colleagues elected him to a series of leadership posts culminating in his 1980 election as Republican Leader, and he won reelection as Leader six more times. Leading the Republican House Minority examines Michel's contribution through a series of essays by congressional scholars in history and political science. The essays examine topics such as Michel's efforts to pass Reagan's tax cuts, strategies for House minority leadership, the 1982 re-election campaign, the differences between Michel and Newt Gingrich, Michel's mid-career transition from protectionism to expansionism, and his retirement one election before the Republicans became the House majority party"--